Prevalence of Musculoskeletal Pain and Its Relation With Weight of Backpacks in School-Going Children in Eastern India - Sankaran, Sindhu; John, Joseph; Patra, Sameer Sekhar; Das, Rashmi Ranjan; Satapathy, Amit Kumar (Frontiers in Pain Research, 2021)
Background: Recently, heavy school bags have come to become a great concern among parents, health professionals as well as the media but evidence for same is limited in Indian context. Aim: To find the prevalence of musculoskeletal pain amongst school going children and its relation with backpack weight Design: Cross sectional study Method: This was carried out among school going children from standard 6th to 10th of age group 10 to 16 years from urban and rural location. Schools were selected randomly from enlisted schools in district of Khurdha, Odisha. A structured questionnaire was administered to assess symptoms of musculoskeletal pain. Anthropometric measurements along with backpack weight were taken. Results: Prevalence of musculoskeletal pain was 18.8% in the last one year. Backpacks are higher among children of urban schools as compared to rural areas. Children from urban schools were more likely to have pain as compared to rural schools (OR 1.61, 95% CI 1.19-2.17). Increased weight of backpack had a higher risk of having pain (OR 1.25, 95% CI 1.07-1.46). Those children having backpack weight higher than maximum recommended backpack weight had almost twice the risk of having musculoskeletal pain (OR 1.65, 95% CI 1.13-2.42). Conclusion: Prevalence of musculoskeletal pain was high in school going children. Children carrying higher backpack weight and higher percentage of backpack to body weight had significant association with musculoskeletal pain. Gender, height, body mass Index and backpack weight to body weight >10% had no association with musculoskeletal pain.